Phylogenetic and Structural Analysis of NIN-Like Proteins With a Type I/II PB1 Domain That Regulates Oligomerization for Nitrate Response - Hsin, Kuan-Ting; Yang, Tzu-Jing; Lee, Yu-Hsuan; Cheng, Yi-Sheng (Frontiers in Plant Science, 2021)
Absorption of macronutrients such as nitrogen is a critical process for land plants. There is little information available on the correlation between the root evolution of land plants and the protein regulation of nitrogen absorption and responses. NIN-like protein (NLP) transcription factors contain a PB1 domain, which may regulate nitrate-response genes and seem to be involved in the adaptation to growing on land in terms of plant root development. In this report, we reveal the NLP phylogeny in land plants and the origin of NLP genes that may be involved in the nitrate-signaling pathway. Our NLP phylogeny showed that duplication of NLP genes occurred before divergence of chlorophyte and land plants. Duplicated NLP genes may lost in most chlorophyte lineages. The NLP genes of bryophytes were initially monophyletic, but this was followed by divergence of lycophyte NLP genes and then angiosperm NLP genes. Among those identified NLP genes, PB1, a protein-protein interaction domain was identified across our phylogeny. To understand how protein-protein interaction mediate via PB1 domain, we examined the PB1 domain of Arabidopsis thaliana NLP7 (AtNLP7) in terms of its molecular oligomerization and function as representative. Based on the structure of the PB1 domain, determined using small-angle x-ray scattering (SAXS) and site-directed mutagenesis, we found that the NLP7 PB1 protein forms oligomers and that several key residues (K867 and D909/D911/E913/D922 in the OPCA motif) play a pivotal role in the oligomerization of NLP7 proteins. The fact that these residues are all conserved across land plant lineages means that this oligomerization may have evolved after the common ancestor of extant land plants colonized the land. It would then have rapidly become established across land-plant lineages in order to mediate protein–protein interactions in the nitrate-signaling pathway.